Cellular Basis of Organotin(IV) Derivatives as Anticancer Metallodrugs: A Review - Syed Annuar, Sharifah Nadhira; Kamaludin, Nurul Farahana; Awang, Normah; Chan, Kok Meng (Frontiers in Chemistry, 2021)
Organotin(IV) compounds have wide applications in industrial and agricultural fields owing to their ability to act as poly(vinyl chloride) stabilizers and catalytic agents as well as their medicinal properties. Moreover, organotin(IV) compounds may have applications as antitumor, anti-inflammatory, antifungal or antimicrobial agents based on the observation of synergistic effects following binding of their respective ligands, resulting in enhancement of their biological activities. In this review, we describe the antiproliferative activities of organotin(IV) compounds in various human cancer cell lines based on different types of ligands. We also discuss the molecular mechanisms through which organotin(IV) compounds induce cell death via apoptosis through the mitochondrial intrinsic pathway. Finally, we present the mechanisms of cell cycle arrest induced by organotin(IV) compounds. Our report provides a basis for studies of the antitumor activities of organotin(IV) compounds and highlights the potential applications of these compounds as anticancer metallodrugs with low toxicity and few side effects.